Electrode
By introducing a polymer layer into the secondary battery electrode, using its PTC effect and oxidation potential characteristics, the fire and explosion problems caused by the short circuit of the secondary battery in an abnormal state are solved, and the stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202380064634.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-19
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-18
AI Technical Summary
Existing secondary batteries are prone to short circuits under overcharging, high temperature exposure or external impact, resulting in an increase in the frequency of ignition or explosion accidents.
An electrode including a polymer layer exhibits PTC effect and oxidation potential controlled according to the target, ensuring excellent electrical properties of the electrode in a normal state, and increasing resistance in an abnormal state to ensure stability.
This electrode does not affect or improve the performance and operation of the secondary battery in normal state, and ensures stability in abnormal states, reducing the risk of ignition or explosion.
Smart Images

Figure CN119856291A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0135150, filed on October 19, 2022, the disclosure of which is incorporated herein by reference in its entirety.
[0002] This specification discloses an electrode and its use. Background Art
[0003] Energy storage technology has expanded its application areas to include mobile phones, tablets and laptops or electric vehicles.
[0004] As the data processing speed of mobile devices such as mobile phones or tablets increases and their usage time increases, secondary batteries having high energy density and working potential, long cycle life, and low self-discharge rate are being developed.
[0005] In addition, as major developed countries curb the production of internal combustion engine-driven vehicles to alleviate global warming and air pollution, major automobile manufacturers have also developed various electric vehicles, and therefore the importance of secondary batteries with high energy density, high discharge voltage and output stability as their driving source has increased.
[0006] However, according to the above-mentioned trend, the frequency of fire or explosion accidents caused by overcharging, high temperature exposure, external impact, etc. is also increasing in devices or cars using secondary batteries as energy sources.
[0007] As a major cause of such accidents, a short circuit phenomenon is known, in which the positive and negative electrodes within an electrode assembly come into direct contact with each other, primarily due to external stimulation. This short circuit phenomenon occurs when a secondary battery is overcharged or exposed to high temperatures or external stimulation, resulting in shrinkage of the separator due to an increase in the internal temperature of the secondary battery, or damage to the internal structure of the secondary battery due to external impact.
[0008] When a short circuit occurs, the migration of lithium ions and electrons is concentrated in the area where the positive and negative electrodes are in direct contact, which promotes internal heating. Consequently, it is known that the volume expands as gas is generated inside the battery, increasing the risk of fire. Summary of the Invention
[0009] Technical issues
[0010] This specification discloses an electrode and its use. This specification is intended to disclose an electrode comprising a polymer layer, wherein the polymer layer exhibits a PTC (positive temperature coefficient) effect and oxidation potential controlled according to a target. This electrode exhibits excellent electrical properties such as low resistance under normal conditions, does not affect or can even improve the performance and operation of a secondary battery, and can ensure stability under abnormal conditions. This specification also discloses a use of an electrode.
[0011] Technical Solution
[0012] In this specification, the term room temperature refers to a natural temperature without heating or cooling, which may refer to, for example, any temperature within the range of 10°C to 30°C, or a temperature of about 23°C or about 25°C.
[0013] Among the physical properties mentioned in this specification, when measuring physical properties affected by temperature, the relevant physical properties are physical properties measured at room temperature unless otherwise specified.
[0014] Unless otherwise specified, the unit of temperature in this specification is degree Celsius (° C.).
[0015] In this specification, the term "normal pressure" refers to natural pressure without any increase or decrease in pressure, which generally refers to a pressure of approximately 730 mmHg to 790 mmHg. Among the physical properties mentioned in this specification, when measuring a physical property affected by pressure, the relevant physical property is the physical property measured under normal pressure unless otherwise specified.
[0016] Among the physical properties mentioned in this specification, when humidity affects the results of measurement, the relevant physical properties are the physical properties measured at humidity under standard conditions, unless otherwise specified.
[0017] The humidity under standard conditions refers to any relative humidity within the range of 40% to 60%, and refers to, for example, a relative humidity of around 55% or 60%.
[0018] In this specification, the term normal state refers to a normal operating state of a secondary battery (eg, a normal charge or discharge state of the secondary battery), or a storage state thereof.
[0019] In this specification, the term abnormal state refers to a dangerous state in which abnormal charge flow, abnormal heating, explosion, or the like occurs due to external impact and / or a short circuit phenomenon, or the like, or in which the probability of occurrence of such an abnormal state increases.
[0020] This specification discloses an electrode.
[0021] The electrode may include: a current collector; an active material layer formed on the current collector; and a polymer layer formed between the current collector and the active material layer. Figure 1 is a cross-sectional view of an exemplary electrode sequentially including a current collector 100, a polymer layer 200, and an active material layer 300. As shown in the figure, the current collector 100, the polymer layer 200, and the active material layer 300 may be in contact with each other. As needed, other elements may be present between the current collector 100 and the polymer layer 200, and / or between the polymer layer 200 and the active material layer 300. In addition, although the figure shows a case where the active material layer 300 is present only on one side of the current collector 100, the active material layer 300 may also be present on both sides of the current collector 100. In this case, the polymer layer 200 may also be present as two layers between each active material layer 300 present on both sides of the current collector 100 and the current collector 100, and may also be present as one layer between any one active material layer 300 present on both sides and the current collector 100.
[0022] The electrode may be, for example, a positive electrode (anode) or a negative electrode (cathode) applied to a secondary battery.
[0023] The polymer layer included in the electrode is a layer including a polymer. Such a polymer may be a conductive polymer described below.
[0024] In the electrode, a polymer layer is provided to exhibit a controlled PTC (positive temperature coefficient) effect. The PTC effect is known to increase electrical resistance depending on temperature. The polymer layer is provided so that the PTC effect occurs at temperatures in abnormal conditions. Therefore, the electrode can exhibit stable performance under normal conditions due to the excellent electrical properties of the polymer layer, while stability can be ensured under abnormal conditions due to the increased resistance of the polymer layer.
[0025] In the electrode, the polymer layer may exhibit a tuned oxidation potential relative to the active material layer.
[0026] For example, the polymer layer in the electrode or the conductive polymer contained in the polymer layer can have a lower oxidation potential than the electrode active material or the active material layer. Through such adjustment, stable performance can be maintained even when the secondary battery using the electrode is repeatedly charged and discharged, or subjected to high-speed charging and / or high-speed discharging.
[0027] Here, the oxidation potential of the conductive polymer or polymer layer is the oxidation potential relative to lithium, which is the oxidation potential for lithium and lithium ions (based on Li / Li + ), and can be measured in the manner described in "4. Oxidation Potential Measurement Method (Conductive Polymer / Polymer Layer)" of the Examples section in this specification.
[0028] Here, the oxidation potential of the electrode active material or active material layer is the oxidation potential relative to lithium, which is the oxidation potential for lithium and lithium ions (based on Li / Li + ), and can be measured in the manner described in "5. Oxidation Potential Measurement Method (Electrode Active Material)" of the Examples section of this specification.
[0029] For example, the electrode may be designed so that the RV of the following equation 1 is within a predetermined range.
[0030] [Equation 1]
[0031] RV=100×Va / Vs
[0032] In Equation 1, Va is the oxidation potential of the electrode active material or active material layer, and Vs is the oxidation potential of the conductive polymer or polymer layer.
[0033] The lower limit of RV in Equation 1 may be approximately 100, 100.5, 101, 101.5, 102, or 102.5, and the upper limit thereof may be approximately 200, 195, 190, 185, 180, 175, 170, 165, 160, 155, 150, 145, 140, 135, 130, 125, 120, 115, 110, 109, 108, 107, 106, 105, 104, or 103. RV may be within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or may be within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0034] In the above equation 1, the oxidation potential Va is determined according to the type of the electrode active material and is not particularly limited. For example, the lower limit of the oxidation potential Va may be about 2.0 V, 2.1 V, 2.2 V, 2.3 V, 2.4 V, 2.5 V, 2.6 V, 2.7 V, 2.8 V, 2.9 V, 3 V, 3.1 V, 3.2 V, 3.3 V, 3.4 V, 3.5 V, 3.6 V, 3.7 V, 3.8 V, 3.9 V or 4.0 V, and the upper limit thereof may be about 5 V, 4.9 V, 4.8 ... The oxidation potential Va may be in the range of equal to or greater than any one of the above lower limits, or in the range of equal to or less than any one of the above upper limits, or in the range of between equal to or less than any one of the above upper limits and equal to or greater than any one of the above lower limits.
[0035] There is no particular limitation on Vs in the above equation 1, as long as it is controlled so that the oxidation potential of the electrode active material or active material layer according to the application satisfies the range of RV. For example, the lower limit of the oxidation potential Vs may be 0 V, 0.1 V, 0.2 V, 0.3 V, 0.4 V, 0,5 V, 0.6 V, 0.7 V, 0.8 V, 0.9 V, 1.0 V, 1.1 V, 1.2 V, 1.3 V, 1.4 V, 1.5 V, 1.6 V, 1.7 V, 1.8 V, 1.9 V, 2.0 V, 2.1 V, 2.2 V, 2.3 V, 2.4 V, 2.5 V, 2.6 V, 2.7 V, 2.8 V, 2.9 V, 3 V, 3.1 V, 3.2 V, 3.3 V, 3.4 V, 3.5 V, 3.6 V, 3.7 V, 3.8 V, 3.9 V, 4. V, 3.6V, 3.7V, 3.8V, 3.9V or 4.0V, and the upper limit can also be 5V, 4.9V, 4.8V, 4.7V, 4.6V, 4.5V, 4.4V, 4.3V, 4.2V, 4.1V, 4.0V, 3.9V, 3.8V, 3.7V, 3.6V, 3.5V, 3.4V, 3.3V, 3.2V, 3.1V, 3.0V, 2.9V, 2.8V, 2.7V, 2.6V, 2.5V, 2.4V, 2.3V, 2.2V, 2.1V or 2.0V. The oxidation potential Vs may be within a range greater than, equal to, or greater than any one of the above lower limits; or within a range less than, equal to, or less than any one of the above upper limits; or may have a range between less than, equal to, or less than any one of the above upper limits and greater than, equal to, or greater than any one of the above lower limits.
[0036] In the electrode, the upper limit of the direct current (DC) resistance of the polymer layer at 25° C. may be 10,000 Ω·cm, 9,500 Ω·cm, 9,000 Ω·cm, 8,500 Ω·cm, 8,000 Ω·cm, 7,500 Ω·cm, 7,000 Ω·cm, 6,500 Ω·cm, 6,000 Ω·cm, 5,500 Ω·cm, 5,000 Ω·cm, 4,500 Ω·cm, 4,000 Ω·cm, 3,500 Ω·cm, 3,000 Ω·cm, 2,500 Ω·cm, 2,000 Ω·cm, 1,500 Ω·cm, 1,000 Ω·cm, or 2,000 Ω·cm. The DC resistance may be within a range of less than or equal to, or less than, any of the above upper limits; or within a range of less than or equal to, or less than, any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The DC resistance is measured in the manner described in “6. DC resistance measurement method” of the embodiment of this specification.
[0037] In the electrode, the upper limit of the alternating current (AC) impedance resistance of the polymer layer may be approximately 1,000Ω, 950Ω, 900Ω, 850Ω, 800Ω, 750Ω, 700Ω, 650Ω, 600Ω, 550Ω, 500Ω, 450Ω, 400Ω, 350Ω, 300Ω, 250Ω, 200Ω, 150Ω, 100Ω, 95Ω, 90Ω, 85Ω, 80Ω, 75Ω, 70Ω, 65Ω, 60Ω, 55Ω, or 50Ω, and the lower limit thereof may be approximately 10Ω, 15Ω, 20Ω, 25Ω, 30Ω, 35Ω, 40Ω, 450Ω, 50Ω, 55Ω, 60Ω, 65Ω, 70Ω, 75Ω, 80Ω, or 85Ω. The AC impedance resistance may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or may be within a range of less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits. The AC impedance resistance is measured as described in "7. Interface Resistance (AC Impedance Resistance)" of the Examples of this specification.
[0038] Since the polymer layer exhibits DC resistance and / or AC impedance resistance, the electrode, or a secondary battery or electrode assembly to which the electrode is applied can be stably operated or stored under normal conditions.
[0039] The polymer layer can exhibit a PTC effect according to target design.
[0040] For example, the polymer layer may exhibit a characteristic in which ΔR1 of the following Equation 2 is within a predetermined range.
[0041] [Equation 2]
[0042] ΔR1=Max{(R n+5 / R n ) / 5}
[0043] In Equation 1, R n R is the DC resistance at any temperature n°C in the range of 25°C to 135°C. n+5 It is the DC resistance at a temperature 5℃ higher than the temperature n℃ ((n+5)℃), Max{(R n+5 / R n ) / 5} was confirmed in the temperature range of 25℃ to 135℃ (R n+5 / R n ) / 5 values.
[0044] The ΔR1 of equation 2 is measured for a coin cell battery using a polymer layer, and the specific method is described in "8. Measurement of Maximum Resistance Change Rate (DC Resistance)" of the embodiment. In the method for determining ΔR1, the initial temperature is 25°C and the final temperature is 135°C. n+5 and R n This is confirmed by measuring the DC resistance at each temperature while increasing the temperature by 5°C from the initial temperature of 25°C. For example, when n is 90, R 95 / R 90 It is the ratio of the DC resistance at 95° C. to the DC resistance at 90° C. When ΔR1 is 100 Ω·cm / ° C. or more at any temperature within the temperature range of 25° C. to 135° C., it means that the resistance increases relatively rapidly at any temperature within the temperature range.
[0045] The lower limit of ΔR1 can be approximately 40, 45, 50, 55, 60, 65, 70, 75, 80, 90, 100, 150, 200, 250, 300, 350, or 400, and its upper limit can be approximately 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250, 200, or 150. The unit of ΔR1 is Ω·cm / °C. ΔR1 can be within a range greater than, equal to, or greater than any of the above lower limits; or it can be within a range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits. These characteristics ensure the stability of secondary batteries and the like under abnormal conditions.
[0046] Confirm the temperature at ΔR1, that is, R n The lower limit of the temperature may be approximately 70°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, or 95°C, and the upper limit may be approximately 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 110°C, 100°C, or 90°C. The temperature may be within a range of less than, equal to, or less than any of the upper limits; or within a range of greater than, equal to, or greater than any of the lower limits; or within a range between less than, equal to, or less than any of the upper limits and greater than, equal to, or greater than any of the lower limits. The temperature is adjusted to a temperature at which an abnormal state occurs or there is a risk of an abnormal state occurring. When a polymer layer exhibiting this characteristic is applied, an electrode, an electrode assembly, or a secondary battery can maintain stable performance even when stored in a normal state at a relatively high temperature and in a charge and discharge state at a high temperature, while ensuring stability under abnormal conditions.
[0047] The polymer may exhibit a property where ΔR2 of the following equation 3 is within a predetermined range.
[0048] [Equation 3]
[0049] ΔR2=Max{(R z+5 / R z ) / 5}
[0050] In Equation 2, R z R is the AC impedance resistance at any temperature n°C in the range of 25°C to 135°C. z+5 is the AC impedance resistance at a temperature 5°C higher than the temperature n°C ((n+5)°C), Max{(R z+5 / R z) / 5} was confirmed in the temperature range of 25℃ to 135℃ (R z+5 / R z ) / 5 values.
[0051] The ΔR2 of equation 3 is measured for a coin cell battery to which a polymer layer is applied. The specific method is described in "9. Measurement of Maximum Resistance Change Rate (AC Impedance)" of the embodiment. In the method for determining ΔR2, the initial temperature is 25°C and the final temperature is 135°C. z+5 and R z This is confirmed by measuring the AC impedance resistance at each temperature while increasing the temperature by 5°C from the initial temperature of 25°C. For example, when n is 90, R 95 / R 90 It is the ratio of the AC impedance resistance at 95° C. to the AC impedance resistance at 90° C. The fact that ΔR2 exhibits 10Ω / ° C. or more at any temperature within the temperature range of 25° C. to 135° C. means that the resistance of the polymer layer increases relatively rapidly at any temperature within the temperature range.
[0052] The lower limit of ΔR2 can be about 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 33, 34, 36, 38, 40, 42 or 44, and the upper limit can be about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 18 or 16. The unit of ΔR2 is Ω / °C. ΔR2 can be less than, equal to, or less than any of the above upper limits, or can be greater than, equal to, or greater than any of the above lower limits, or can have a range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits. Through this characteristic, the electrode using the polymer layer can ensure the stability of the secondary battery, etc. under abnormal conditions.
[0053] The temperature when ΔR2 in the above range is confirmed, that is, R zThe lower limit of the temperature may be approximately 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, or 95°C, and the upper limit may be approximately 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 110°C, 100°C, or 90°C. The temperature may be within a range of less than, equal to, or less than any of the upper limits; or within a range of greater than, equal to, or greater than any of the lower limits; or within a range between less than, equal to, or less than any of the upper limits and greater than, equal to, or greater than any of the lower limits. This temperature is adjusted to a temperature at which an abnormal state occurs or there is a risk of an abnormal state occurring. When a polymer layer exhibiting this characteristic is applied, an electrode, an electrode assembly, or a secondary battery can maintain stable performance even when stored in a normal state at a relatively high temperature and in a charge and discharge state at a high temperature, while ensuring stability under abnormal conditions.
[0054] The conductive polymer forming the polymer layer can be controlled so that the polymer layer exhibits an oxidation potential and a PTC effect controlled thereby.
[0055] The conductive polymer included in the polymer layer may be a polythiophene or a thiophene polymer. In this specification, the term polythiophene or thiophene polymer refers to a polymer containing a certain level or more of thiophene units. The term "thiophene unit" refers to a monomer unit formed by polymerizing a thiophene-based monomer, and the term "thiophene-based monomer" refers to a monomer containing a thiophene backbone.
[0056] The term "monomer unit" refers to a structure in which monomers are polymerized and included in a polymer.
[0057] The lower limit of the ratio of the thiophene units in the polythiophene or thiophene polymer may be about 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, 85 mol%, 90 mol% or 95 mol%, based on the total moles of all monomer units in the polythiophene or thiophene polymer. The upper limit may be about 99 mol%, 97 mol%, 95 mol%, 93 mol%, 91 mol%, 89 mol%, 87 mol%, 85 mol%, 83 mol%, 81 mol%, 79 mol%, 77 mol%, 75 mol%, 73 mol%, 71 mol%, 69 mol%, 67 mol%, 65 mol%, 63 mol%, 61 mol%, 59 mol%, 57 mol%, 55 mol%, 53 mol%, or 51 mol%. The ratio of thiophene units may be within a range greater than, equal to, or greater than any of the above lower limits, or may be within a range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits.
[0058] As the thiophene unit contained in the polythiophene, a thiophene unit having a hydrocarbon functional group can be used.
[0059] In this specification, the term "hydrocarbon functional group" refers to a monovalent hydrocarbon group (i.e., a monovalent functional group composed of carbon and hydrogen), or a monovalent functional group including a monovalent hydrocarbon group. Therefore, in addition to carbon and hydrogen, the hydrocarbon functional group may also include other atoms. Examples of monovalent hydrocarbon groups include alkyl, alkynyl, or alkenyl groups, and examples of monovalent functional groups including a monovalent hydrocarbon group include alkoxy, alkylcarbonyl, or alkylcarbonyloxy, but the types of hydrocarbon functional groups are not limited thereto.
[0060] The lower limit of the carbon number of the hydrocarbon functional group may be about 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12, and the upper limit may be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, or 3. The carbon number may be in a range greater than, equal to, or greater than any of the above lower limits; or in a range less than, equal to, or less than any of the above upper limits; or in a range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits.
[0061] The carbon number may be the total carbon number of the hydrocarbon functional group or the monovalent hydrocarbon group contained therein, or the carbon number of the hydrocarbon chain having the longest straight-chain structure included in the hydrocarbon functional group or the monovalent hydrocarbon group contained therein. That is, the hydrocarbon functional group or the monovalent hydrocarbon group may have a straight-chain structure or a branched-chain structure, and even in the case of a branched-chain structure, the carbon number constituting the longest straight-chain in the branched-chain structure may be within the above-mentioned range. For example, if the branched-chain structure is 2-ethylhexyl, the carbon atoms constituting the longest chain are 6.
[0062] The alkyl, alkenyl, alkynyl, alkoxy, alkylcarbonyl or alkylcarbonyloxy groups as hydrocarbon functional groups may also be substituted by one or more substituents.
[0063] In the conductive polymer, the molar ratio of thiophene units having hydrocarbon functional groups may have a lower limit of approximately 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, or 85 mol%, and an upper limit of approximately 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol%, or 45 mol%. This ratio is based on the total number of moles of all monomer units contained in the polymer. This ratio may be within a range greater than, equal to, or greater than any of the aforementioned lower limits; within a range less than, equal to, or less than any of the aforementioned upper limits; or within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0064] Since the conductive polymer contains the thiophene unit, the polymer or polymer layer containing it exhibits an appropriate PTC (positive temperature coefficient) effect and its surface properties are adjusted, thereby ensuring excellent adhesion in electrodes or current collectors and exhibiting an appropriate level of oxidation potential.
[0065] Hydrocarbon functional groups are functional groups that impart appropriate fluidity to the polymerization process of the conductive polymer or to the conductive polymer itself. These functional groups impart appropriate fluidity to the monomer mixture and diffuse within the monomer mixture, enabling efficient polymerization. Furthermore, conductive polymers with these functional groups, due to their appropriate fluidity, can form a stable and uniform polymer layer between the current collector and the active material layer.
[0066] During the drying or annealing process (heat treatment process) applied during the formation of the polymer layer, the hydrocarbon functional groups are appropriately oriented, thereby also imparting appropriate PTC effects and oxidation potential characteristics to the polymer.
[0067] When a certain amount of thermal energy is applied, the hydrocarbon functional groups vibrate due to the heat, and this vibration (thermal vibration) promotes the dedoping of anions bound to the polymer, thereby inducing an increase in resistance. The temperature at which thermal vibration occurs can be controlled by the length and / or amount of the hydrocarbon functional groups. For example, at the same temperature, the thermal vibration of relatively long chains is greater than that of relatively short chains. As a result, long chains can induce a resistance-increasing effect at relatively low temperatures. Therefore, the desired PTC effect can be set by controlling the length and / or ratio of the hydrocarbon functional groups.
[0068] As the thiophene unit having a hydrocarbon functional group, the polymer may include a first thiophene unit having a long-chain hydrocarbon functional group and a second thiophene unit having a short-chain hydrocarbon functional group.
[0069] The term "long-chain hydrocarbon functional group" is a hydrocarbon functional group according to the above, but refers to a hydrocarbon functional group in which the carbon number is adjusted to above a certain level.
[0070] The term "short-chain hydrocarbon functional group" is a hydrocarbon functional group according to the above, but refers to a hydrocarbon functional group in which the carbon number is adjusted below a certain level.
[0071] The lower limit of the carbon number of the long-chain hydrocarbon functional group may be about 10, 11 or 12, and the upper limit thereof may be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11 or 10. The carbon number contained in the long-chain hydrocarbon functional group may be in a range of greater than, equal to, or greater than any of the above lower limits; or may be in a range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits.
[0072] The lower limit of the carbon number of the short-chain hydrocarbon functional group may be about 3, 4, 5, 6, 7 or 8, and the upper limit thereof may be about 9, 8, 7 or 6. The carbon number contained in the short-chain hydrocarbon functional group may be within a range of less than, equal to, or less than any of the above upper limits; or may be within a range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits.
[0073] The specific description of the long-chain hydrocarbon functional group and the short-chain hydrocarbon functional group is the same as that of the hydrocarbon functional group except for the carbon number.
[0074] In the conductive polymer, the ratio of the total number of moles of the first and second thiophene units may have a lower limit of approximately 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, or 85 mol%, and an upper limit of approximately 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol%, or 45 mol%. This ratio is based on the total number of moles of all monomer units contained in the polymer. This ratio may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or may be within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0075] The ratio (M2 / M1) of the number of moles of the second thiophene unit (M2) to the number of moles of the first thiophene unit (M1) in the conductive polymer may have a lower limit of about 0.01, 0.05, 0.1, 0.5, 1, 1.5, or 2, and an upper limit of about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.8, 0.7, 0.6, or 0.55. This ratio may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or may be within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0076] At such a ratio, the conductive polymer or polymer layer exhibits an appropriate PTC (positive temperature coefficient) effect, and its surface characteristics are adjusted, thereby ensuring excellent adhesion in the electrode or current collector.
[0077] The polymer may further include a thiophene unit having a polar functional group together with the thiophene unit having a hydrocarbon functional group as the thiophene unit.
[0078] The term "polar functional group" refers to a functional group containing one or more polar atoms, such as oxygen and / or nitrogen. Examples of such functional groups include, but are not limited to, carboxyl, hydroxyl, amino, cyano, nitro, ether, or the functional group of Formula 1 below.
[0079] [Formula 1]
[0080]
[0081] In Formula 1, L3 is a single bond, an alkylene group, or an alkylidene group, L4 is an alkylene group or an alkylidene group, R8 is hydrogen or an alkyl group, and n is any number.
[0082] In Formula 1, L3 being a single bond means that L3 does not exist, and the oxygen atom between L4 and L3 is directly connected to the skeleton of the monomer or polymer.
[0083] In this specification, the term "alkylene" refers to a divalent functional group formed by removing hydrogen atoms from two different carbon atoms in an alkane, and the term alkylidene refers to a divalent functional group formed by removing two hydrogen atoms from one carbon atom in an alkane.
[0084] In this specification, unless otherwise specifically defined, the term "alkylene" may be an alkylene group having 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms, or 2 to 4 carbon atoms. The alkylene group may be linear, branched, or cyclic, and may also be optionally substituted with one or more substituents.
[0085] In this specification, unless otherwise specifically limited, the term "alkylidene group" may be an alkylidene group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms. The alkylidene group may be linear or branched or cyclic, and may also be optionally substituted with one or more substituents.
[0086] In one example, the alkyl group of R8 in Formula 1 may be an alkyl group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms, or may be a methyl group or an ethyl group. The alkyl group may be linear, branched, or cyclic, and may be linear or branched as appropriate.
[0087] In Formula 1, the lower limit of n may be approximately 1, 2, 3, or 4, and the upper limit thereof may be approximately 10, 9, 8, 7, 6, 5, 4, or 3. n may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or may be within a range of less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0088] By applying the polar functional group, the polymer layer including the conductive polymer can be combined with other layers to have an appropriate bonding force, and a desired protective function can be effectively achieved by uniformly forming the conductive polymer layer.
[0089] In the case where the thiophene unit having a polar functional group is present in the conductive copolymer, the thiophene unit having a polar functional group may be present in such a manner that the total number of moles of the thiophene unit having a hydrocarbon functional group per mole of the thiophene unit having a polar functional group is within a predetermined range.
[0090] For example, the ratio of the total number of moles of thiophene units having hydrocarbon functional groups (M) to the number of moles of thiophene units having polar functional groups (M3) (i.e., M / M3) may have a lower limit of about 1, 2, 3, 4, 5, 6, 8, or 8.5 moles, and an upper limit thereof may be about 500, 450, 400, 350, 300, 250, 200, 150, 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 9.5, or 9 moles. This ratio may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or may be within a range of less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0091] Such a thiophene unit may be, for example, a unit of Formula 2 below.
[0092] [Formula 2]
[0093]
[0094] In Formula 2, R1 and R2 may each independently be hydrogen, a polar functional group, or a hydrocarbon functional group.
[0095] In another example, R1 and R2 in Formula 1 may also be connected to each other to form a divalent functional group of Formula 3 below.
[0096] [Formula 3]
[0097]
[0098] In Formula 3, L1 and L2 may each independently be a single bond, an alkylene group, or an alkylidene group, and R3 and R4 may each independently be hydrogen, a polar functional group, or a hydrocarbon functional group.
[0099] For example, if the unit of Formula 2 is a thiophene unit having a hydrocarbon functional group as described above, one or more of R1 and R2 can be a hydrocarbon functional group (if R1 and R2 are not connected), or one or more of R3 and R4 can be a hydrocarbon functional group (if R1 and R2 are not connected).
[0100] For example, if the unit of Formula 2 is a thiophene unit having a polar functional group as described above, one or more of R1 and R2 can be a polar functional group (if R1 and R2 are not connected), or one or more of R3 and R4 can be a polar functional group (if R1 and R2 are not connected).
[0101] For example, if the unit of Formula 2 above is the above-mentioned first thiophene unit, one or more of R1 and R2 can be the above-mentioned long-chain hydrocarbon functional group (if R1 and R2 are not connected), or one or more of R3 and R4 can be the above-mentioned long-chain hydrocarbon functional group (if R1 and R2 are not connected).
[0102] For example, if the unit of Formula 2 above is the above-mentioned second thiophene unit, one or more of R1 and R2 can be the above-mentioned short-chain hydrocarbon functional group (if R1 and R2 are not connected), or one or more of R3 and R4 can be the above-mentioned short-chain hydrocarbon functional group (if R1 and R2 are not connected).
[0103] Specific descriptions of the hydrocarbon functional group, polar functional group, long-chain hydrocarbon functional group, and short-chain hydrocarbon functional group are as described above.
[0104] In addition, the specific descriptions of the alkylene group and the alkylidene group of the above Formula 3 are the same as those described in the above Formula 1.
[0105] The polymer may include another additional monomer unit along with the thiophene unit. For example, the additional monomer may be included to adjust the oxidation potential of the polymer. For example, as desired, the conductive polymer may include a unit that exhibits a lower or higher oxidation potential than the thiophene unit.
[0106] The weight average molecular weight (Mw) of the polymer can be within a predetermined range. The lower limit of the weight average molecular weight of the polymer can be 10,000 g / mol, 11,000 g / mol, 12,000 g / mol, 13,000 g / mol, 14,000 g / mol, 15,000 g / mol, 16,000 g / mol, 17,000 g / mol, 18,000 g / mol, 19,000 g / mol, 20,000 g / mol, 21,000 g / mol, 22,000 g / mol, 23,000 g / mol, 24,000 g / mol, 25,000 g / mol, 26,000 g / mol, 27,000 g / mol, 28,000 g / mol, 29,000 g / mol, 30,000 g / mol, 31,000 g / mol, 32,000 g / mol, 33,000 g / mol, 34,000 g / mol, 35 The upper limit of the present invention may be about 9,000 g / mol, 30,000 g / mol, 31,000 g / mol, 32,000 g / mol, 33,000 g / mol, 34,000 g / mol, 35,000 g / mol, 36,000 g / mol, 37,000 g / mol, 38,000 g / mol, 39,000 g / mol or 40,000 g / mol, and the upper limit may be 2,000,000 g / mol, 1,500,000 g / mol, 1,000,000 g / mol, 900,000 g / mol, 800,000 g / mol, 700,000 g / mol, 600,000 g / mol mol, 500,000g / mol, 400,000g / mol, 300,000g / mol, 295,000g / mol, 290,000g / mol, 285,000g / mol, 280,000g / mol, 275,000g / mol, 270,000g / mol, 2 65,000g / mol, 260,000g / mol, 255,000g / mol, 250,000g / mol, 245,000g / mol, 240,000g / mol, 235,000g / mol, 230,000g / mol, 225,000g / mol, 220,00 0g / mol, 215,000g / mol, 210,000g / mol, 205,000g / mol, 200,000g / mol, 195,000g / mol, 190,000g / mol, 185,000g / mol, 180,000g / mol, 175,000g / mo l, 170,000g / mol, 165,000g / mol, 160,000g / mol, 155,000g / mol, 150,000g / mol, 145,000g / mol, 140,000g / mol, 135,000g / mol, 130,000g / mol, 125,The weight average molecular weight may be in the range of less than, equal to, or less than any of the above upper limits; or in the range of greater than, equal to, or greater than any of the above lower limits; or in the range between less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits.
[0107] The molecular weight distribution of the polymer, i.e., the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), can be within a predetermined range. The lower limit of the molecular weight distribution can be about 2, 2.5, 3, 3.5, or 4, and the upper limit thereof can be about 8, 7.5, 7, 6.5, 6, 5.5, 5, 4.5, 4, or 3.5. The molecular weight distribution can be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or can also have a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits.
[0108] The weight average molecular weight and molecular weight distribution are measured in the manner described in "2. GPC (Gel Permeation Chromatography)" in the Example section of this specification.
[0109] The polymer layer may include a polymer. The polymer layer may be composed solely of a polymer, or may further include any other necessary additives in addition to the polymer. By using a polymer, a desired electrode can be effectively formed. In one example, based on the total weight of the polymer layer, the lower limit of the amount of the polymer in the polymer layer may be about 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt% or 95 wt%, and the upper limit may be about 100 wt%, 95 wt%, 90 wt% or 85 wt%. This ratio is based on the total weight of the polymer layer. The range of this ratio may be less than, equal to, or less than any one of the above upper limits; or greater than, equal to, or greater than any one of the above lower limits; or it may also have a range between less than, equal to, or less than any one of the above upper limits and greater than, equal to, or greater than any one of the above lower limits.
[0110] The thickness of the polymer layer can be appropriately controlled according to the target. For example, the lower limit of the thickness can be about 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, and the upper limit can be about 2μm, 1.5μm, 1μm, 950nm, 900nm, 850nm, 800nm, 750nm, 700nm, 650nm, 600nm, 550nm, 500nm, 450nm, 400nm, 350nm or 300nm. The thickness can be less than, equal to, or less than any one of the above upper limits; or within the range of greater than, equal to, or greater than any one of the above lower limits; or it can also have a range between less than, equal to, or less than any one of the above upper limits and greater than, equal to, or greater than any one of the above lower limits. The thickness can be measured in the manner described in "3. Thickness Measurement" of the Examples section of this specification.
[0111] There is no particular limitation on the current collector included in the electrode, and a current collector generally used for a positive electrode or a negative electrode may be used.
[0112] If the current collector has conductivity and does not cause chemical changes in an application device such as a secondary battery, there is no particular limitation on its type, size, shape, etc. Examples of materials that can be used as current collectors include copper, aluminum, or stainless steel whose surfaces are surface-treated with carbon, nickel, titanium, or silver. The current collector may be in the form of a film, sheet, foil, mesh, porous body, foam, or non-woven fabric containing the above materials. In some cases, a known surface treatment may also be performed on the surface of the current collector to improve adhesion to other layers such as a polymer layer or an active material layer.
[0113] Such a current collector may generally have a thickness in the range of 3 μm to 500 μm, but is not limited thereto.
[0114] A commonly used layer can also be used as the active material layer.
[0115] Typically, the active material layer includes an electrode active material. There is no particular limitation on the specific type of the electrode active material, and generally, materials forming a positive electrode or a negative electrode can be used.
[0116] For example, when the active material layer is a positive electrode active material layer, the electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, V2O5 or Cu2V2O7; LiNi 1-c2 M c2 Ni-type lithium nickel oxide represented by O2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1); lithium nickel cobalt manganese (NCM) composite oxide, lithium nickel cobalt manganese aluminum (NCMA) composite oxide, and LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions, etc., but are not limited thereto.
[0117] When the active material layer is a negative electrode active material layer, as the electrode active material, for example, a compound capable of reversibly intercalating and deintercalating lithium can be used. Specific examples include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides capable of doping and dedoping lithium, such as SiO a (0<a<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material comprising a metal compound and a carbonaceous material, such as a Si-C composite material or a Sn-C composite material, etc., and any one or a mixture of two or more of the above can be used.
[0118] A metallic lithium film can also be used as a negative electrode active material, and as a carbon material, low-crystalline carbon and high-crystalline carbon can also be used. As low-crystalline carbon, soft carbon and hard carbon are representative, and as high-crystalline carbon, high-temperature calcined carbon, such as amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch, and coke derived from petroleum and coal tar pitch are representative.
[0119] The content of the electrode active material in the active material layer may be in the range of approximately 80 wt % to 99.5 wt %, or in the range of 88 wt % to 99 wt %, relative to the total weight of the active material layer, but the ratio may vary depending on the purpose or design of the electrode.
[0120] The active material layer may further include a binder. The binder is used to improve the adhesion between the active materials and the adhesion between the active material layer and the current collector. There is no particular limitation on the example of the binder, and one or more selected from the following can be used, for example, PVDF (polyvinylidene fluoride), PVA (polyvinyl alcohol), SBR (styrene-butadiene rubber), PEO (polyethylene oxide), CMC (carboxymethyl cellulose), cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate polymer (polyethylene-co-vinyl acetate) and polyarylate.
[0121] In one example, the content of the binder in the active material layer may be in the range of 0.1 to 10 parts by weight or 0.5 to 5 parts by weight relative to 100 parts by weight of the electrode active material, but is not limited thereto.
[0122] The active material layer may further include a conductive material as needed. If the conductive material has conductivity and does not cause chemical changes in the secondary battery, there is no particular limitation, and any known material can be used. For example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes (CNTs); metal powders such as fluorocarbons, aluminum or nickel powders; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0123] In one example, the conductive material may be included in an amount of 0.1 to 20 parts by weight, or 0.3 to 10 parts by weight, relative to 100 parts by weight of the electrode active material, but is not limited thereto.
[0124] In addition to the above-mentioned components, the active material layer may optionally further include any necessary known components.
[0125] This specification also discloses a method for manufacturing an electrode.
[0126] The manufacturing method may include the step of forming a polymer layer on the current collector, and may include the step of forming an active material layer on the polymer layer.
[0127] There is no particular limitation on the method for forming the polymer layer on the current collector. For example, the polymer layer can be formed by diluting the conductive polymer and other additives (as needed) in a suitable solvent to prepare a coating solution, applying the coating solution on the current collector, and then drying.
[0128] In another example, the polymer layer may also be formed by directly polymerizing monomers forming a conductive polymer on the current collector.
[0129] There are no particular limitations on the method for preparing the coating composition for forming the polymer layer and the coating method thereof, and known coating methods can be applied. Furthermore, there are no particular limitations on the method for polymerizing the conductive polymer, and known methods can be applied. For example, methods utilizing oxidative polymerization or free radical reactions are generally known as methods for preparing polythiophene, and such methods can also be applied to the process of forming the conductive polymer in this application.
[0130] The prepared coating composition can be used to form a polymer layer on a current collector. The process can generally include a step of applying the coating composition to the current collector and a step of heat-treating the applied coating composition. In this process, the properties of the polymer layer can also be controlled by the conditions of the heat treatment.
[0131] For example, the temperature T of the heat treatment and / or the time H of the heat treatment may be controlled.
[0132] For example, the lower limit of the temperature T may be around 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, and the upper limit may be 300°C, 295°C, 290°C, 285°C, 280°C, 275°C, 270°C, 265°C, 260°C, 255°C, 250°C, The temperature may be around 245°C, 240°C, 235°C, 230°C, 225°C, 220°C, 215°C, 210°C, 205°C, 200°C, 195°C, 190°C, 185°C, 180°C, 175°C, 170°C, 165°C, 160°C, 155°C, 150°C, 145°C, 140°C, 135°C, 130°C, 125°C, 120°C, 115°C, 110°C, 105°C, 100°C, 95°C, or 90°C. The temperature may be within a range of less than, equal to, or less than any of the upper limits; or within a range of greater than, equal to, or greater than any of the lower limits; or within a range between less than, equal to, or less than any of the upper limits and greater than, equal to, or greater than any of the lower limits. Within this range, the arrangement of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0133] In order to achieve the above purpose, the product (T×H) of the heat treatment temperature T and the time H can be adjusted. For example, the lower limit of the product (T×H) of the heat treatment temperature T and the time H can be about 0.01°C·hour, 0.05°C·hour, 0.1°C·hour, 0.2°C·hour, 0.3°C·hour, 0.5°C·hour, 1°C·hour, 5°C·hour, 10°C·hour, 15°C·hour, 20°C·hour, 25°C·hour, 30°C·hour, 35°C·hour, 40°C·hour, 45°C·hour, 50°C·hour, 75°C·hour, 100°C·hour, 110°C·hour, 120°C·hour or 130°C·hour, and the upper limit can be about 100°C·hour, 110°C·hour, 120°C·hour or 130°C·hour. The temperature is 100000℃·hour, 95000℃·hour, 90000℃·hour, 85000℃·hour, 80000℃·hour, 75000℃·hour, 70000℃·hour, 65000℃·hour, 60000℃·hour, 55000℃·hour, 50000℃·hour, 45000℃·hour, 40000℃·hour, 35000℃·hour, 30000℃·hour, 25000℃·hour, 20000℃·hour, 15000℃·hour, 10000℃·hour, 9500℃·hour hours, 9000℃·hours, 8500℃·hours, 8000℃·hours, 7500℃·hours, 7000℃·hours, 6500℃·hours, 6000℃·hours, 5500℃·hours, 5000℃·hours, 4500℃·hours, 4000℃·hours, 3500℃·hours, 3000℃·hours, 2500℃·hours, 2000℃·hours, 1500℃·hours, 1400℃·hours, 1300℃·hours, 1200℃·hours, 1100℃·hours, 1000℃·hours, 900℃·hours Hour, 800°C hour, 700°C hour, 600°C hour, 500°C hour, 400°C hour, 300°C hour, 200°C hour, 100°C hour, 90°C hour, 80°C hour, 70°C hour, 60°C hour, 50°C hour, 45°C hour, 40°C hour, 35°C hour, 30°C hour, 25°C hour, 20°C hour, 15°C hour, 10°C hour, 5°C hour, 4°C hour, 3°C hour, 2°C hour, 1°C hour or about 0.5°C hour. The product (T×H) may be in a range of less than, equal to, or less than any of the upper limits; or in a range of greater than, equal to, or greater than any of the lower limits; or in a range of less than, equal to, or less than any of the upper limits and greater than, equal to, or greater than any of the lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, and thus, desired properties can be ensured.
[0134] To more effectively ensure the desired properties, the heat treatment can be performed in two steps.
[0135] For example, the heat treatment may include: a step of performing a first heat treatment on the coating composition at a first temperature T1 for a first time H1; and a step of performing a second heat treatment on the coating composition at a second temperature T2 for a second time H2, wherein the temperatures T1 and T2 are different from each other, and / or the times H1 and H2 are different from each other.
[0136] For example, the lower limit of the temperature T1 may be about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, and the upper limit thereof may be 300°C, 295°C, 290°C, 285°C, 280°C, 275°C, The temperature may be around 270°C, 265°C, 260°C, 255°C, 250°C, 245°C, 240°C, 235°C, 230°C, 225°C, 220°C, 215°C, 210°C, 205°C, 200°C, 195°C, 190°C, 185°C, 180°C, 175°C, 170°C, 165°C, 160°C, 155°C, 150°C, 145°C, or 140°C. This temperature may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits. Within this range, the arrangement of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0137] For example, the lower limit of the product of the temperature T1 and the time H1 of the first heat treatment (T1×H1) may be about 0.01°C·hour, 0.05°C·hour, 0.1°C·hour, 0.2°C·hour or 0.3°C·hour, and the upper limit may be 1000°C·hour, 900°C·hour, 800°C·hour, 700°C·hour, 600°C·hour, 500°C·hour, 400°C·hour, 300°C·hour , 200°C·hour, 100°C·hour, 90°C·hour, 80°C·hour, 70°C·hour, 60°C·hour, 50°C·hour, 45°C·hour, 40°C·hour, 35°C·hour, 30°C·hour, 25°C·hour, 20°C·hour, 15°C·hour, 10°C·hour, 5°C·hour, 4°C·hour, 3°C·hour, 2°C·hour, 1°C·hour, or about 0.5°C·hour. The product (T1×H1) may be within a range of less than, equal to, or less than any of the upper limits; or within a range of greater than, equal to, or greater than any of the lower limits; or within a range between less than, equal to, or less than any of the upper limits and greater than, equal to, or greater than any of the lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0138] For example, the lower limit of the heat treatment temperature T2 of the second heat treatment may be about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, and the upper limit thereof may be 300°C, 295°C, 290°C, 285°C, 280°C, 275°C, 270°C, 285°C or 290°C. The temperature may be about 65°C, 260°C, 255°C, 250°C, 245°C, 240°C, 235°C, 230°C, 225°C, 220°C, 215°C, 210°C, 205°C, 200°C, 195°C, 190°C, 185°C, 180°C, 175°C, 170°C, 165°C, 160°C, 155°C, 150°C, 145°C, 140°C, 135°C, or 130°C. This temperature may be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits. Within this range, the arrangement of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0139] The product of the second heat treatment temperature T2 and the time H2 (T2×H2) may be adjusted. For example, the lower limit of the product of the heat treatment temperature T and the time H (T2×H2) can be about 10℃·hour, 15℃·hour, 20℃·hour, 25℃·hour, 30℃·hour, 35℃·hour, 40℃·hour, 45℃·hour, 50℃·hour, 75℃·hour, 100℃·hour, 110℃·hour, 120℃·hour or 130℃·hour, and the upper limit can also be about 1000℃·hour, 900℃·hour, 800℃·hour, 700℃·hour, 600℃·hour, 500℃·hour, 400℃·hour, 300℃·hour, 200℃·hour, 180℃·hour, 160℃·hour, 150℃·hour, 145℃·hour, 140℃·hour, 135℃·hour or 130℃·hour. The product (T2×H2) can be within a range of less than, equal to, or less than either of the aforementioned upper limits; within a range of greater than, equal to, or greater than either of the aforementioned lower limits; or within a range between less than, equal to, or less than either of the aforementioned upper limits and greater than, equal to, or greater than either of the aforementioned lower limits. Within this range, the arrangement of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0140] In the above case, the lower limit of the ratio (T1 / T2) of the first heat treatment temperature (T1) to the second heat treatment temperature (T2) can be approximately 0.1, 0.3, 0.5, 0.7, 0.9, 0.95, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, or 1.07, and the upper limit can be approximately 10, 9, 8, 7, 6, 5, 4, 3, 2, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, or 1.1. The ratio (T1 / T2) can be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits. Within this range, the arrangement of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0141] In this case, the lower limit of the ratio (H2 / H1) of the first heat treatment time H1 to the second heat treatment time H2 can be approximately 0.5, 1, 3, 5, 7, 9, 10, 11, 12, 13, 14, 14.5, or 15, and the upper limit can be approximately 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 19, 18, 17, 16, 15.5, or 15. The ratio H2 / H1 can be within a range of less than, equal to, or less than any of the aforementioned upper limits; or within a range of greater than, equal to, or greater than any of the aforementioned lower limits; or within a range between less than, equal to, or less than any of the aforementioned upper limits and greater than, equal to, or greater than any of the aforementioned lower limits. Within this range, the arrangement of the hydrocarbon groups in the conductive polymer can be appropriately adjusted, thereby ensuring desired performance.
[0142] In the above-mentioned manufacturing process, after the coating and / or polymerization process, post-treatment such as an appropriate drying process may be additionally performed.
[0143] In addition, there is no particular limitation on the method for forming the active material layer on the polymer layer. Typically, the active material layer is formed by coating a slurry comprising an electrode active material, a binder, and a conductive material on a current collector (on the polymer layer), followed by drying and then rolling. This known method can also be applied to the present application.
[0144] This specification also discloses an electrode assembly or electrochemical element, such as a secondary battery, comprising the electrode. If the electrode assembly or electrochemical element comprises the electrodes described above, there are no particular restrictions on the specific details of other configurations. For example, as is well known, an electrode assembly may comprise a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, wherein either or both of the positive electrode and the negative electrode may be the electrodes described above. In addition, an electrochemical element, such as a secondary battery, may comprise an electrode or electrode assembly and an electrolyte, etc.
[0145] Beneficial effects
[0146] This specification discloses an electrode and its use. The electrode includes a polymer layer that exhibits a PTC (positive temperature coefficient) effect and oxidation potential that are controlled according to a target. This electrode exhibits excellent electrical properties such as low resistance under normal conditions without affecting or even improving the performance and operation of a secondary battery, and can ensure stability under abnormal conditions. This specification also discloses a use of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0147] Figure 1 is a cross-sectional view of an exemplary electrode.
[0148] Figure 2 The NMR analysis results of the monomers prepared in the preparation examples.
[0149] Figure 3 The performance evaluation results of the electrode of Example 1.
[0150] Figure 4 The performance evaluation results of the electrode of Example 1.
[0151] Figure 5 The performance evaluation results of the electrode of Comparative Example 1.
[0152] Figure 6 The performance evaluation results of the electrode of Comparative Example 1. Detailed implementation manners
[0153] Hereinafter, electrodes and the like disclosed in this specification will be specifically described through examples and comparative examples, but the scope of electrodes and the like is not limited by the following examples.
[0154] 1. NMR analysis method
[0155] It is performed at room temperature using an NMR spectrometer including a Bruker UltraShield spectrometer (300 MHz) with a 5 mm triple resonance probe. 1 1H-NMR analysis. The sample is diluted to a concentration of about 10 mg / ml in a solvent (CDCl3) for NMR measurement and used, and the chemical shift is expressed in ppm.
[0156] 2. GPC (gel permeation chromatography)
[0157] The molecular weight characteristics are measured using GPC (gel permeation chromatography). The sample is placed in a 5 mL vial and diluted to a concentration of about 1 mg / mL with chloroform. Then, the standard sample for calibration and the sample to be analyzed are filtered through a syringe filter (pore size: 0.45 μm) and then measured. As the analysis program, Empower 3 of Waters is used, and the weight-average molecular weight (Mw) and number-average molecular weight (Mn) are obtained respectively by comparing the elution time of the sample with the calibration curve, and the molecular weight distribution (PDI) is calculated by the ratio (Mw / Mn). The measurement conditions of GPC are as follows.
[0158] <GPC measurement conditions>
[0159] Apparatus: Waters’ 2414
[0160] Column: Use 3 Styragel from Waters
[0161] Solvent: THF (tetrahydrofuran)
[0162] Column temperature: 35°C
[0163] Sample concentration: 1 mg / mL, 1 μL injection
[0164] Standard sample: polystyrene (Mp: 3900000, 723000, 316500, 52200, 31400, 7200, 3940, 485)
[0165] 3. Thickness measurement
[0166] The electrodes were cross-sectioned using an ion milling device (Hitachi, IM5000), and images were taken using a SEM (scanning electron microscope) (JEOL, JSM-7200F) to measure the thickness of the polymer layer, etc. The conditions for forming the cross section by ion milling were: the device was set to cross-section cutting mode, the speed (reciprocating motion / minute) was 3, the acceleration voltage was 6.0 kV, the discharge voltage was 15 kV, the current was 150 μA, and the time was 4 hours.
[0167] 4. Oxidation Potential Measurement Method (Conductive Polymer / Polymer Layer)
[0168] The oxidation potential was measured in the following manner. A layer having a thickness of about 10 μm (hereinafter referred to as a polymer layer) was formed on an aluminum foil (Al foil) having a thickness of about 15 μm using the conductive polymer whose oxidation potential was to be measured. The polymer layer was formed by applying the same method as that used in Example 1 below.
[0169] Afterwards, a separator and a lithium film were laminated onto the polymer layer to produce a laminate comprising aluminum foil, polymer layer, separator, and lithium film, and the laminate was punched into a circular shape with a diameter of approximately 1.4 cm. Coin cells were fabricated using the circular punched laminate and an electrolyte (using a Welcos CR2032 coin cell kit).
[0170] As a separator, the WL20C model from W Scope of South Korea was used; as a lithium membrane, a membrane with a thickness of about 100 μm was used; as an electrolyte, a 1M LiPF6 solution (solvent: EC / DMC / EMC=3 / 4 / 3 (mass ratio), EC: ethylene carbonate, DMC: dimethyl carbonate, EMC: ethyl methyl carbonate) produced by Enchem was used.
[0171] The oxidation potential of the button cell was measured at 25°C using an electrochemical meter (potentiostat) (Princeton Applied Research, PARASTAT-MC). The oxidation potential was measured by measuring CV (cyclic voltammetry) in the range of 1.5 V to 5.5 V at a scan rate of 0.17 mV / sec to 0.5 mV / sec. The oxidation potential is the oxidation potential relative to lithium, which is based on the relationship between lithium and lithium ions (Li / Li). +) to measure.
[0172] 5. Oxidation potential measurement method (electrode active materials)
[0173] Regarding the oxidation potential of the electrode active material, a coin cell was manufactured by using an electrode manufactured using the electrode active material, and the related coin cell was measured.
[0174] The slurry was prepared by preparing the electrode active material to be tested, the conductive material (ECP (Ketjen Black) 0.5%, SFG (Trimrex Graphite) 0.4%, DB (Denka Carbon Black) 0.4%, PVDF (polyvinylidene fluoride) and NMP (N-methyl-2-pyrrolidone) in a weight ratio of 75:1:1:23 (electrode active material: conductive material: PVDF: NMP). The slurry was coated on the current collector with a doctor blade, dried at room temperature (about 25°C), and then kept in a drying oven at 130°C for about 30 minutes, and then rolled to form an electrode active material layer with a thickness of about 53 μm, thereby manufacturing the electrode.
[0175] An electrode active material to be tested is used as the electrode active material.
[0176] Rolling is performed so that the porosity of the active material layer is about 25%. The porosity of the active material layer is calculated by comparing the ratio of the difference between the actual density and the density after rolling. Methods for obtaining the porosity in this way are known.
[0177] Aluminum foil with a thickness of about 15 μm was used as the current collector.
[0178] Afterwards, a separator and a lithium film were laminated on the electrode active material layer of the electrode to produce a laminated body in which the electrode / separator / lithium film was laminated, and the laminated body was punched into a circular shape with a diameter of approximately 1.4 cm. A button cell was manufactured using the circular punched laminate and an electrolyte (using a Welcos CR2032 button cell kit).
[0179] As a separator, the WL20C model from W Scope of South Korea was used; as a lithium membrane, a membrane with a thickness of about 100 μm was used; as an electrolyte, a 1M LiPF6 solution (solvent: EC / DMC / EMC=3 / 4 / 3 (mass ratio), EC: ethylene carbonate, DMC: dimethyl carbonate, EMC: ethyl methyl carbonate) produced by Enchem was used.
[0180] The oxidation potential of the button cell was measured using an electrochemical meter (potentiostat) (Princeton Applied Research, PARASTAT-MC) at 25° C. The oxidation potential was measured by CV (cyclic voltammetry) in the range of 1.5 V to 5.5 V at a scan rate of 0.17 mV / sec to 0.5 mV / sec.
[0181] The oxidation potential is the oxidation potential relative to lithium, which is based on the relationship between lithium and lithium ions (Li / Li + ) to measure.
[0182] 6. DC resistance measurement method
[0183] The DC resistance was evaluated using the same coin cell used in "4. Oxidation Potential Measurement Method (Conductive Polymer / Polymer Layer)." However, the thickness of the polymer layer in the coin cell was set to approximately 200 nm. A voltage of 4.3 eV was applied to the coin cell at room temperature (25°C) for 10 minutes, and the DC resistance was measured using a Fluke digital multi-function tester (Fluke-87-5).
[0184] 7. Interface resistance (AC impedance resistance)
[0185] The interface resistance was evaluated by EIS (electrochemical impedance spectroscopy) using the same button cell used in “4. Oxidation potential measurement method (conductive polymer / polymer layer)”. However, the thickness of the polymer layer in the button cell was set to about 200 nm. A voltage of 4.3 V was applied to the button cell at room temperature (25° C.) for 10 minutes, and the interface resistance obtained in the high-frequency region was measured by the Nyquist plot obtained by the EIS measurement method at 50,000 Hz to 0.1 Hz. An electrochemical meter (potentiostat) (Princeton Applied Research, PARASTAT-MC) was used as the EIS measurement device.
[0186] 8. Measurement of maximum resistance change rate (DC resistance)
[0187] The maximum resistance change rate ΔR1 is determined according to the following equation 1.
[0188] [Equation 1]
[0189] ΔR1=Max{(Rn+5 / Rn) / 5}
[0190] The above-mentioned ΔR1 is measured in the following manner.
[0191] The button cell for DC resistance measurement (the button cell used in "6. DC resistance measurement method") is placed in the center of a convection oven (Jeotech, OF3-05W), and the temperature of the oven is set to rise from an initial temperature of 25°C to a final temperature of 135°C at 5°C per minute. The button cell is connected to a resistance measuring multimeter (Fluke digital multifunction tester (Fluke-87-5)) outside the oven for resistance measurement. Subsequently, the DC resistance is measured at various temperatures while the temperature is set to rise. That is, the DC resistance is measured at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C and 130°C, respectively. Maintain each temperature for 1 minute according to the settings, and measure the DC resistance after 1 minute at the relevant temperature. The DC resistance at each temperature is used as Rn in Equation 1 above. The DC resistance at a temperature 5°C higher than the relevant temperature is used as Rn+5 in Equation 1 above. In the measured DC resistance, the DC resistance at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C and 125°C is respectively designated as Rn, 21 values of (Rn+5 / Rn) / 5 are obtained in the temperature range of 25°C to 130°C, and then the maximum value among them is designated as Max{(Rn+5 / Rn) / 5}(=ΔR1) of the above formula 1, and the temperature n°C at the maximum value (Rn+5 / Rn) / 5 is designated as the on-set temperature (On-Set temperature).
[0192] 9. Measurement of maximum resistance change rate (AC impedance)
[0193] The maximum resistance change rate ΔR2 is determined according to the following equation 2.
[0194] [Equation 2]
[0195] ΔR2=Max{(Rz+5 / Rz) / 5}
[0196] ΔR2 is measured in the following manner.
[0197] The button cell for AC impedance resistance measurement (the button cell used in “7. Interface resistance (AC impedance resistance)”) was placed in the center of a convection oven (Jeotech, OF3-05W), and the temperature of the oven was set to rise from an initial temperature of 25°C to a final temperature of 135°C at 5°C per minute. The button cell was connected to a resistance measuring device (the measuring device used in “7. Interface resistance (AC impedance resistance)”) outside the oven for resistance measurement. Subsequently, the AC impedance resistance at each temperature was measured while the temperature was raised as set. That is, the AC impedance resistance was measured at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C and 130°C, respectively. According to the setting contents, each temperature was maintained for 1 minute, and the AC impedance resistance was measured when 1 minute passed at the relevant temperature.
[0198] The AC impedance resistance at each temperature is designated as Rz in the above equation 2, and the AC impedance resistance at a temperature 5°C higher than the relevant temperature is designated as Rz+5 in the above equation 2. Among the measured AC impedance resistances, the AC impedance resistances at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, and 125°C are designated as Rz, respectively. 21 values of (Rz+5 / Rz) / 5 are obtained within the temperature range of 25°C to 130°C, and the maximum value among them is designated as Max{(Rz+5 / Rz) / 5}(=ΔR2) in the above equation 2, and the temperature z°C at which the maximum value (Rz+5 / Rz) / 5 occurs is designated as the starting temperature.
[0199] The AC impedance resistance is resistance obtained from a semicircle in a high-frequency region in a Nyquist plot obtained by applying a voltage of 4.3 V for 10 minutes and measuring using EIS at 50,000 Hz to 0.1 Hz.
[0200] Preparation Example 1. Synthesis of Monomer (A)
[0201] The monomer of the following formula A was synthesized in the following manner.
[0202] [Formula A]
[0203]
[0204] In 100 ml of toluene, 1.372 g (12.02 mmol, 1 eq) of 3-methoxythiophene and 3 g (16.83 mmol, 1.4 eq) of triethylene glycol monomethyl ether were dissolved and mixed together with 230 mg of p-toluenesulfonic acid (p-TsOH). While the mixture was refluxed at 120° C. for reaction, the methanol produced by the reaction (ether exchange) was removed by a 4A type molecular sieve filled in an extractor (Soxhlet extractor). The reactants were refluxed for 24 hours and then quenched with water and extracted with ethyl acetate, then washed with brine and dried over magnesium sulfate (MgSO4). The solvent was removed using a rotary evaporator, and the residue was purified by column chromatography eluting with dichloromethane / hexane (2:1) to obtain the target compound (monomer (A)). The results of NMR analysis of the target compound (monomer (A)) are shown in Figure 2 middle.
[0205] Preparation Example 2. Synthesis of Conductive Polymer (Polythiophene (A))
[0206] To a solution in which 3.20 g (19.71 mmol, 3 eq) of iron (III) chloride was dissolved in 150 ml of dichloromethane, 1 g (3.94 mmol, 0.6 eq) of 3-dodecylthiophene, 0.33 g (1.97 mmol, 0.3 eq) of 3-hexylthiophene, and 0.16 g (0.66 mmol, 0.1 eq) of the monomer (A) of Preparation Example 1 were introduced and polymerized at 30° C. for 24 hours to prepare polythiophene (A). In the conductive polymer (A), the molar ratio of the 3-dodecylthiophene unit (I), the 3-hexylthiophene unit (II), and the monomer (A) unit (III) of Preparation Example 1 was approximately 3.94:1.97:0.66 (I:II:III).
[0207] The polymerization solution was placed in a permeable membrane with a MWCO (molecular weight cut-off) of 5000, and then immersed in 200 ml of acetonitrile solvent to remove unreacted iron (III) chloride, monomers, and low molecular weight oligomers. The residue precipitated in the permeable membrane was washed with methanol and dried at 60° C. for 12 hours to obtain polythiophene (A).
[0208] The weight average molecular weight (Mw) and number average molecular weight (Mn) of polythiophene (A) are 118,000 g / mol and 24,500 g / mol, respectively, and the oxidation potential is about 3.7 V.
[0209] Example 1.
[0210] An aluminum foil having a thickness of about 15 μm was used as the current collector. The polythiophene (A) of Preparation Example 2 was dispersed in a solvent (chloroform) at a concentration of about 2.0 wt % to prepare a coating solution. The coating solution was applied to the current collector using a rod coating method. Subsequently, the current collector having the coating formed thereon was kept in a drying oven at 140° C. for about 4 minutes and again kept at about 130° C. for 1 hour to form a layer (polymer layer) having a thickness of about 200 nm.
[0211] Subsequently, an active material layer is formed on the conductive polymer layer. The active material layer is formed using a slurry. The slurry is prepared by configuring a positive electrode active material, a conductive material (ECP (Ketjen Black) 0.5%, SFG (Trimrex Graphite) 0.4%, DB (Denka Carbon Black) 0.4%), PVDF (polyvinylidene fluoride) and NMP (N-methyl-2-pyrrolidone) in a weight ratio of 75:1:1:23 (electrode active material: conductive material: PVDF: NMP). The slurry is applied to the conductive polymer layer with a doctor blade, dried at room temperature, and then kept in a drying oven at 130°C for about 30 minutes, and then rolled to form an active material layer with a thickness of about 53 μm (based on the electrode active material, weighing 0.03 g and a porosity of 18%).
[0212] Here, LCO (LiCoO 2 ) was used as the electrode active material, and the oxidation potential of the electrode active material measured in the manner described in “5. Oxidation Potential Measurement Method (Electrode Active Material)” was approximately 3.8 V.
[0213] Comparative Example 1.
[0214] Except when the active material layer is formed on the conductive polymer layer, NCM (Li[N 0.8 Co 0.1 Mn 0.1 ]O2) as the electrode active material, an electrode was manufactured in the same manner as in Example 1. The oxidation potential of the electrode active material (NCM) measured in the manner described in "5. Oxidation Potential Measurement Method (Electrode Active Material)" was approximately 3.7 V.
[0215] Test Example 1. Charge-discharge test
[0216] The charge-discharge test was carried out by manufacturing button cells. A button cell kit of CR2032 standard (WelcosCR2032 button cell kit) was used to manufacture the button cell. The electrode manufactured in the embodiment or comparative example was used as the positive electrode, and a lithium film (thickness: about 100 μm) was used as the negative electrode. As the electrolyte, a 1M LiPF6 solution (solvent: EC / DMC / EMC=3 / 4 / 3 (mass ratio), EC: ethylene carbonate, DMC: dimethyl carbonate, EMC: ethyl methyl carbonate) of Enchem's product was used, and a PE (polyethylene) separator (Korea W-Scope, WL20C model) was used as the separator.
[0217] The charge-discharge test was carried out using a button cell, and 6 cycles were performed using the constant current constant voltage (CC-CV) method in the following order: 0.1C charge / 0.1C discharge (cycle 1), 0.2C charge / 0.2C discharge (cycle 2), 0.5C charge / 0.1C discharge (cycle 3), 0.5C charge / 0.5C discharge (cycle 4), 0.5C charge / 1C discharge (cycle 5) and 0.5C charge / 2C discharge (cycle 6).
[0218] Figure 3 and Figure 4 is a charge-discharge curve of the electrode of Example 1, Figure 5 and Figure 6 3 is a charge-discharge curve showing the results of a charge-discharge test performed using the electrode of Comparative Example 1.
[0219] exist Figure 3 and Figure 4 In the figure, LCO(Ref) refers to a charge-discharge curve of a charge-discharge test conducted on an electrode manufactured in the same manner as in Example 1 but without forming a conductive polymer layer, and LCO(SFL) refers to a charge-discharge curve of a charge-discharge test conducted on an electrode including a current collector layer, a conductive polymer layer, and an active material layer manufactured in Example 1.
[0220] exist Figure 5 and Figure 6 In the figure, NCM(Ref) refers to a charge-discharge curve of a charge-discharge test performed on an electrode manufactured in the same manner as in Comparative Example 1 but without forming a conductive polymer layer, and NCM(SFL) refers to a charge-discharge curve of a charge-discharge test performed on an electrode manufactured in Comparative Example 1 and including a current collector layer, a conductive polymer layer, and an active material layer.
[0221] By comparing the accompanying drawings, it can be confirmed that in the case of Example 1, the oxidation potential of the conductive polymer of the conductive polymer layer (polymer layer) is lower than the oxidation potential of the electrode active material, and the efficiency does not decrease even after charging and discharging, but in the case of Comparative Example 1, the efficiency of the button battery decreases after charging and discharging.
[0222] Test Example 2. PTC effect test
[0223] Among the electrodes manufactured as described above, the evaluation results of the DC resistance, interface resistance, ΔR1, the onset temperature of ΔR1, ΔR2, and the onset temperature of ΔR2 of the electrode of Example 1 are shown in Table 1 below.
[0224] In Table 1 below, Ref. is the result when only the formation conditions of the polymer layer were changed and other conditions were the same as in Example 1 when manufacturing button batteries for evaluating DC resistance, interface resistance, ΔR1, the starting temperature of ΔR1, ΔR2, and the starting temperature of ΔR2.
[0225] That is, in Table 1 below, the results of Example 1 are the results of a button battery including the following polymer layer, which is formed by coating a coating liquid prepared by dispersing the polythiophene (A) of Preparation Example 2 in a solvent (chloroform) at a concentration of about 2.0 weight % on a current collector (aluminum foil) by a rod coating method, and keeping the current collector with the coating formed thereon in a drying oven at 140°C for about 4 minutes, and then keeping it at about 130°C for about 1 hour. Ref. is the result of a button battery including the following polymer layer, which is formed by coating the same coating liquid as above on the same current collector (aluminum foil) by a rod coating method, and keeping the current collector with the coating formed thereon in a drying oven at 90°C for about 20 minutes.
[0226] [Table 1]
[0227]
[0228] It can be confirmed from Table 1 that by applying a specific conductive polymer, a PTC (positive temperature coefficient) effect according to a target design can be obtained, and even when the same conductive polymer is applied, the PTC effect can be additionally controlled according to the formation method.
Claims
1. An electrode, comprising: current collector; an active material layer formed on the current collector and comprising an electrode active material; and a polymer layer, located between the current collector and the active material layer and comprising a conductive polymer, The oxidation potential of the conductive polymer or the polymer layer is lower than the oxidation potential of the electrode active material or the active material layer.
2. The electrode according to claim 1, wherein The RV of equation 1 below is greater than 100: [Equation 1] RV=100×Va / Vs Wherein, Va is the oxidation potential of the electrode active material or the active material layer, and Vs is the oxidation potential of the conductive polymer or the polymer layer.
3. The electrode according to claim 2, wherein The oxidation potential Va is in the range of 2V to 5V.
4. The electrode according to claim 2, wherein The oxidation potential Vs is in the range of 0V to 5V.
5. The electrode according to claim 1, wherein The polymer layer has a DC resistance of 10,000 Ω·cm or less at 25° C.
6. The electrode according to claim 1, wherein The AC impedance resistance of the polymer layer is 1,000Ω or less.
7. The electrode according to claim 1, wherein The ΔR1 of equation 2 below is above 100Ω·cm / ℃: [Equation 2] ΔR1=Max{(R n+5 / Rn) / 5} Among them, R n is the DC resistance of the polymer layer at any temperature n°C in the range of 25°C to 135°C, R n+5 is the DC resistance of the polymer layer at a temperature 5°C higher than the temperature n°C, i.e. (n+5)°C, Max{(R n+5 / R n ) / 5} is confirmed in the temperature range of 25℃ to 135℃ (R n+5 / R n ) / 5 values.
8. The electrode according to claim 7, wherein The temperature at which ΔR1 is confirmed to be 100 Ω·cm / °C or more is 80°C or more.
9. The electrode according to claim 1, wherein The ΔR2 of equation 3 below is above 10Ω / °C: [Equation 3] ΔR2=Max{(R z+5 / R z ) / 5} Among them, R z is the AC impedance resistance of the polymer layer at any temperature n°C in the range of 25°C to 135°C, R z+5 is the AC impedance resistance of the polymer layer at a temperature 5°C higher than the temperature n°C, i.e. (n+5)°C, Max{(R z+5 / R z ) / 5} is confirmed in the temperature range of 25℃ to 135℃ (R z+5 / R z ) / 5 values.
10. The electrode according to claim 9, wherein It was confirmed that the temperature at which ΔR2 was 10Ω / °C or more was 80°C or more.
11. The electrode according to claim 1, wherein The conductive polymer is a polythiophene comprising a thiophene unit having a hydrocarbon functional group.
12. The electrode according to claim 11, wherein The polythiophene includes, as the thiophene units, a first thiophene unit having a hydrocarbon functional group having 10 or more carbon atoms and a second thiophene unit having a hydrocarbon functional group having 9 or less carbon atoms.
13. The electrode according to claim 11, wherein The polythiophene includes 30 mol % or more of thiophene units having a hydrocarbon functional group.
14. The electrode according to claim 12, wherein A ratio M2 / M1 of the mole number M2 of the second thiophene unit to the mole number M1 of the first thiophene unit is in the range of 0.01 to 100.
15. The electrode according to claim 11, wherein The polythiophene further includes a thiophene unit having a polar functional group.
16. The electrode according to claim 15, wherein The polythiophene contains, per mole of the thiophene unit having a polar functional group, 1 mole to 500 moles of the thiophene unit having a hydrocarbon functional group.
17. An electrode assembly comprising a positive electrode, a negative electrode and a separator between the positive electrode and the negative electrode, in, The positive electrode or the negative electrode is the electrode according to any one of claims 1 to 16. 18 . A secondary battery comprising the electrode assembly according to claim 17 .
Citation Information
Patent Citations
Method and device for providing customized cultural and art contents curation and for recommending mate playing the contents with user
KR1020220135150A